Preparation method of super-hydrophobic TPU foam for oil-water separation and super-hydrophobic TPU foam

By using thermoplastic polyurethane (TPU) and modification treatment technology, efficient superhydrophobic TPU foam is prepared, which solves the problems of complex manufacturing of existing materials and the reduction of hydrophobicity, and achieves efficient oil-water separation and long-term stable use effects.

CN119505362APending Publication Date: 2025-02-25ENG MANAGEMENT CENT OF CHINA STATE SHIPBUILDING CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411553847.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The manufacturing process of existing oil-water separation materials is complex, the material has poor hydrophobicity, fragile surface structure, reduced use time efficiency and reduced hydrophobicity.

Method used

Thermoplastic polyurethane (TPU) was used as the porous matrix, and superhydrophobic TPU foam was obtained by freeze-drying and modification treatment, further improving the hydrophobicity of the foam by adhering silica nanoparticles and polydimethylsiloxane (PDMS).

Benefits of technology

Efficient oil-water separation is achieved, and the foam maintains efficient hydrophobicity, and the efficiency of 41.2m3m2h-1 is maintained even after ten oil-water separation cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505362A_ABST
    Figure CN119505362A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of super-hydrophobic TPU (thermoplastic polyurethane) foam for oil-water separation and the super-hydrophobic TPU foam. The preparation method comprises the following steps: S1, preparing super-hydrophobic thermoplastic polyurethane, namely a porous matrix of the TPU foam; s2, modifying the porous matrix to obtain the super-hydrophobic TPU foam. According to the prepared super-hydrophobic TPU foam, thermoplastic polyurethane, namely TPU, serves as a porous matrix of the super-hydrophobic foam, silicon dioxide nanoparticles are attached to the surface of the porous matrix of the super-hydrophobic TPU foam, and the super-hydrophobic TPU foam is obtained. The problems that in the prior art, the manufacturing process of materials is very complex, the hydrophobicity of the materials is poor, the surface structure is fragile, and in the application process, the efficiency is reduced along with the use time, and the hydrophobicity is reduced are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil-water separation materials, in particular to a preparation method of super-hydrophobic TPU foam for oil-water separation and the super-hydrophobic TPU foam. Background Art

[0002] Oil spills can cause many environmental problems. Conventional oil removal technologies such as biological treatment or incineration have the problems of high cost, low efficiency and secondary pollution. In recent years, many researchers have developed hydrophobic materials that can selectively adsorb oil and less water for collecting oil spills, such as aerogels, polymer foams, polymer microspheres and polymer bundles.

[0003] Although the existing technology has made significant progress, there are still several problems that have not been solved. The material manufacturing process of the existing technology is very complicated; in addition, the materials of the existing technology have poor hydrophobicity and fragile surface structure. During the application process, the efficiency decreases and the hydrophobicity decreases with the use time. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method of super-hydrophobic TPU foam for oil-water separation and super-hydrophobic TPU foam, so as to solve the problems of the materials in the prior art that the manufacturing process is very complicated, the material has poor hydrophobicity, the surface structure is fragile, and the efficiency decreases and the hydrophobicity decreases with the use time during the application process.

[0005] The present invention provides a method for preparing a super-hydrophobic TPU foam for oil-water separation, comprising the following steps:

[0006] S1, preparing a porous matrix of superhydrophobic thermoplastic polyurethane, i.e. TPU foam;

[0007] S2, modifying the porous matrix to obtain superhydrophobic TPU foam.

[0008] Wherein, step S1 specifically includes the following steps:

[0009] S101, mixing TPU particles and dioxane at a ratio of 0.03-0.05 g / mL, stirring to form a uniform solution.

[0010] S102, after cooling the uniform solution obtained in step S101 to room temperature, put it into a stirring kettle, add deionized water in a volume ratio of 2:100-4:100, stir, and obtain a mixed solution.

[0011] S103, cooling the mixed solution obtained in step S102 at a temperature of -8 to -4°C until the TPU is completely phase-separated.

[0012] S104, placing the mixture obtained in step 103 in a freeze-drying container at 80° C. and 8 Pa for 72 hours to obtain a porous matrix of superhydrophobic TPU foam.

[0013] Step S2 specifically includes the following steps:

[0014] S201, mixing PDMS and silica nanoparticles in a mass ratio of 1:3-1:5 to obtain a solid mixture of PDMS and silica nanoparticles.

[0015] S202, mixing the solid mixture of PDMS and silica nanoparticles obtained in step S201 with ethanol at a ratio of 0.2-0.6 g / 100 mL, stirring to obtain a uniform solution.

[0016] S203, immersing the porous matrix of the super-hydrophobic TPU foam obtained in step S1 into the uniform solution obtained in step S202.

[0017] S204, placing the porous matrix of the super-hydrophobic TPU foam immersed in step S203 in a 60° C. forced air oven for 1-2 hours to promote ethanol volatilization and PDMS curing, so that the silica nanoparticles adhere to the porous matrix surface of the super-hydrophobic TPU foam to obtain a super-hydrophobic TPU foam.

[0018] In step S101, the stirring temperature is 35-40° C. and the stirring time is 3-4 hours.

[0019] In step S102, the stirring rate is set to 400-600 rpm, and the stirring time is 2-3 hours.

[0020] In step S103, the mixed solution obtained in step S102 is placed in a refrigerator at a temperature of -8 to -4°C and cooled for 12 to 14 hours to achieve complete phase separation of TPU.

[0021] In step S202, the stirring temperature is 60-70°C and the stirring time is 1-2 hours to obtain a uniform solution.

[0022] In step S203, the immersion time is 80-120 seconds.

[0023] The present invention also provides a super-hydrophobic TPU foam. The super-hydrophobic TPU foam is obtained by using thermoplastic polyurethane, namely TPU, as a porous matrix of the super-hydrophobic foam and attaching silicon dioxide nanoparticles to the surface of the porous matrix of the super-hydrophobic TPU foam.

[0024] The beneficial effects of the present invention are as follows: the super-hydrophobic TPU foam provided by the present invention uses thermoplastic polyurethane (TPU) as the porous matrix of the super-hydrophobic foam. TPU is an easily available polymer with high hydrophobicity and high chemical stability. The porous matrix is ​​obtained by a thermal shock non-solvent induced phase separation method with the help of additional water, and the contact angle is 134°. In order to further improve the hydrophobicity of the foam, a modified solution containing silica nanoparticles and polydimethylsiloxane (PDMS) is used. The silica nanoparticles provide nanoscale roughness to the film, while the PDMS acts as an adhesive to fix the silica nanoparticles on the foam. The modified foam exhibits super-hydrophobicity with a water contact angle of 155°. The TPU foam can be used as a selective filtration membrane to achieve oil-water separation, and it still maintains 41.2 m even after ten oil-water separation cycles. 3 m 2 h -1 efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The preparation flow chart of the super hydrophobic TPU foam for oil-water separation of the present invention;

[0026] Figure 2 This is a schematic diagram of the contact angle test result of deionized water on the porous substrate obtained in step S1 of Example 1;

[0027] Figure 3 This is a schematic diagram of the contact angle test results of deionized water of the super-hydrophobic TPU foam obtained in step S2 of Example 1;

[0028] Figure 4 This is a schematic diagram of the microscopic morphology test results of the porous substrate obtained in step S1 of Example 1;

[0029] Figure 5 This is a schematic diagram of the microscopic morphology test results of the super-hydrophobic TPU foam obtained in step S2 of Example 1;

[0030] Figure 6 Schematic diagram of a homemade oil filtration device used to test the oil filtration ability of the super-hydrophobic TPU foam obtained in step S2 of Example 1. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0032] Reference Figure 1As shown, the method for preparing super hydrophobic TPU foam for oil-water separation provided by an embodiment of the present invention comprises the following steps:

[0033] S1. Preparation of porous matrix of superhydrophobic TPU foam:

[0034] S101, TPU particles and dioxane are mixed at a ratio of 0.03-0.05 g / mL, and rapidly stirred at 35-40° C. for 3-4 hours to form a uniform solution.

[0035] S102, after cooling the uniform solution obtained in step S101 to room temperature, put it into a stirring kettle, add deionized water in a volume ratio of 2:100-4:100, set the stirring rate to 400-600 rpm, stir for 2-3 hours, and obtain a mixed solution.

[0036] S103, placing the mixed solution obtained in step S102 in a refrigerator set at a temperature of -8 to -4°C for 12 to 14 hours to achieve complete phase separation of TPU.

[0037] S104, placing the mixture obtained in step 103 in a freeze-drying container at 80°C and 8 Pa for 72 hours to obtain a porous matrix of superhydrophobic TPU foam.

[0038] S2. Modify the porous matrix to obtain super-hydrophobic TPU foam:

[0039] S201, mixing PDMS and silica nanoparticles in a mass ratio of 1:3-1:5 to obtain a solid mixture of PDMS and silica nanoparticles.

[0040] S202, mixing the solid mixture of PDMS and silica nanoparticles obtained in step S201 with ethanol at a ratio of 0.2-0.6 g / 100 mL, and magnetically stirring at 60-70° C. for 1-2 hours to obtain a uniform solution.

[0041] S203, immersing the porous matrix of the super-hydrophobic TPU foam obtained in step S1 into the uniform solution obtained in step S202, the immersion time being 80-120 seconds.

[0042] S204, placing the porous matrix of the super-hydrophobic TPU foam immersed in step 203 in a 60° C. forced air oven for 1-2 hours to promote ethanol volatilization and PDMS curing, so that the silica nanoparticles are firmly attached to the surface of the porous matrix to obtain a super-hydrophobic TPU foam.

[0043] Preferably, the principle of preparing the porous matrix in step S1 is as follows: in the mixed solution prepared in step S102, the polymer chains of TPU can move freely, and the mixed solution will undergo phase separation during the cooling process in step S103, and the solution will gradually be divided into two parts, namely, a polymer-rich phase and a solvent-rich phase; as the temperature decreases, dioxane with a freezing point of 12° C. in the solvent-rich phase will gradually form ice crystals, at which time, deionized water in the mixed solution will be separated from the solvent-rich phase and distributed on the surface of the polymer-rich phase; as the temperature further decreases, deionized water also forms smaller ice crystals, which changes the morphology of the polymer-rich phase; in the subsequent freeze-drying process in step S104, dioxane ice crystals sublimate to form larger pores; similarly, deionized water ice crystals will also sublimate, leaving smaller pores on the polymer surface; therefore, the addition of deionized water can enhance the porosity of the foam, form a hierarchical rough structure, and facilitate the construction of a superhydrophobic surface;

[0044] Preferably, the principle of attaching the silica nanoparticles to the porous matrix in step S2 is that PDMS is a good adhesive that can fix the silica nanoparticles on the porous matrix, and the silica nanoparticles attached to the porous matrix achieve a super-hydrophobic nanoscale microscopic surface morphology, thereby improving the hydrophobicity of the porous matrix.

[0045] Example 1

[0046] S1. Preparation of porous matrix of superhydrophobic TPU foam:

[0047] S101, mixing TPU particles and dioxane at a ratio of 0.03 g / mL, and rapidly stirring at 40° C. for 3 hours to form a uniform solution;

[0048] S102, cooling the uniform solution obtained in step S101 to room temperature, placing it in a stirring kettle, adding deionized water at a volume ratio of 3:100, setting the stirring rate to 400 rpm, stirring for 3 hours to obtain a mixed solution;

[0049] S103, placing the mixed solution obtained in step S102 in a refrigerator set at -4°C for 12 hours to achieve complete phase separation of TPU;

[0050] S104, placing the mixture obtained in step 103 in a freeze-drying container at 80° C. and 8 Pa for 72 hours to obtain a porous matrix of superhydrophobic TPU foam;

[0051] S2. Modify the porous matrix to obtain super-hydrophobic TPU foam:

[0052] S201, mixing PDMS and silica nanoparticles in a mass ratio of 1:4 to obtain a solid mixture of PDMS and silica nanoparticles;

[0053] S202, mixing the solid mixture of PDMS and silica nanoparticles obtained in step S201 with ethanol at a ratio of 0.5 g / 100 mL, and magnetically stirring at 60° C. for 1 hour to obtain a uniform solution;

[0054] S203, immersing the porous matrix of the super-hydrophobic TPU foam obtained in step S1 into the uniform solution obtained in step S202 for 80 seconds;

[0055] S204, placing the porous matrix of the super-hydrophobic TPU foam immersed in step 203 in a 60° C. forced air oven for 2 hours to promote ethanol volatilization and PDMS curing, so that the silica nanoparticles are firmly attached to the surface of the porous matrix to obtain a super-hydrophobic TPU foam.

[0056] Preferably, the principle of preparing the porous matrix in step S1 is as follows: in the mixed solution prepared in step S102, the polymer chains of TPU can move freely, and the mixed solution will undergo phase separation during the cooling process in step S103, and the solution will gradually be divided into two parts, namely, a polymer-rich phase and a solvent-rich phase; as the temperature decreases, dioxane with a freezing point of 12° C. in the solvent-rich phase will gradually form ice crystals, at which time, deionized water in the mixed solution will be separated from the solvent-rich phase and distributed on the surface of the polymer-rich phase; as the temperature further decreases, deionized water also forms smaller ice crystals, which changes the morphology of the polymer-rich phase; in the subsequent freeze-drying process in step S104, dioxane ice crystals sublimate to form larger pores; similarly, deionized water ice crystals will also sublimate, leaving smaller pores on the polymer surface; therefore, the addition of deionized water can enhance the porosity of the foam, form a hierarchical rough structure, and facilitate the construction of a superhydrophobic surface;

[0057] Preferably, the principle of attaching the silica nanoparticles to the porous matrix in step S2 is that PDMS is a good adhesive that can fix the silica nanoparticles on the porous matrix, and the silica nanoparticles attached to the porous matrix achieve a super-hydrophobic nanoscale microscopic surface morphology, thereby improving the hydrophobicity of the porous matrix.

[0058] Performance test of Example 1:

[0059] (I) Contact angle test:

[0060] The contact angle test was performed at room temperature using a contact angle goniometer (model: SL200KS, company: KINO, USA). The volume of the deionized water droplet was 2.5 μL. Figure 2 The contact angle test result of deionized water on the porous substrate obtained in step S1 of Example 1 is shown in FIG. Figure 2It can be seen that the contact angle of deionized water on the porous substrate obtained in step S1 of Example 1 is 134°, which proves that the porous substrate has good hydrophobicity. Figure 3 The contact angle test result of deionized water of the super hydrophobic TPU foam obtained in step S2 of Example 1 is shown in FIG. Figure 3 It can be seen that the contact angle of deionized water of the superhydrophobic TPU foam obtained in step S2 of Example 1 is 155°, which proves that the modification operation in step S2 can well improve the hydrophobicity of the porous matrix, and proves that the superhydrophobic TPU foam proposed in the present invention has excellent hydrophobicity.

[0061] (II) Microscopic morphology test:

[0062] The porous matrix obtained in step S1 and the super-hydrophobic TPU foam obtained in step S2 of Example 1 were tested for microscopic morphology by scanning electron microscopy (SEM). The microscopic morphology test results of the porous matrix and the super-hydrophobic TPU foam are shown in the attached figure. Figure 4 and attached Figure 5 In. Contrast Figure 4 and Figure 5 It can be seen that PDMS is a good adhesive that can fix silica nanoparticles on the porous matrix. The silica nanoparticles attached to the porous matrix achieve super-hydrophobic nanoscale microscopic surface morphology, thereby improving the hydrophobicity of the porous matrix; at the same time, the nanoscale microscopic surface morphology improves the oil adsorption capacity.

[0063] (III) Oil adsorption capacity test:

[0064] The mass of the dry TPU foam was measured with an analytical balance, recorded as m0; the dry TPU foam was immersed in oil for 1 minute, then taken out and the mass was measured on an analytical balance, recorded as mt, and the oil adsorption capacity was quantitatively defined by the absorption capacity (Q):

[0065] Q = mt / m0;

[0066] In Example 1, the absorption capacity of the obtained super hydrophobic TPU foam is 54.11 g -1 , proving that the super-hydrophobic TPU foam provided by the present invention has good oil adsorption capacity;

[0067] (IV) Oil filtration capacity test:

[0068] Place the super hydrophobic TPU foam on the Figure 6 In the homemade oil filtration device shown, oil-water separation is achieved by gravity drive;

[0069] The oil filtration efficiency is calculated as follows:

[0070] E=V / St

[0071] Where E is the oil filtration efficiency, V is the volume of separated organic solvent, S is the surface area of ​​TPU membrane, and t is the separation time.

[0072] In Example 1, the oil filtration efficiency of the obtained super hydrophobic TPU foam is 41.2 m 3 m 2 h -1 , proving that the super-hydrophobic TPU foam provided by the present invention has good oil filtration efficiency;

[0073] (V) Oil filtration capacity test after multiple uses:

[0074] On the basis of test (IV), the experiment was repeated several times. After 10 repeated experiments, the oil filtration efficiency of the super hydrophobic TPU foam obtained in Example 1 could still be maintained at 41.2 m 3 m 2 h -1 , proving that the super-hydrophobic TPU foam provided by the present invention has good reusability.

[0075] According to Example 1 and its performance test experiment, it is proved that: compared with the prior art, the super-hydrophobic TPU foam and its preparation method for oil-water separation provided by the embodiment of the present invention overcome the problems that the manufacturing process of the material in the prior art is very complicated, the material hydrophobicity is poor, the surface structure is fragile, and the efficiency decreases and the hydrophobicity decreases during the application process as the use time decreases. The material provided by the embodiment of the present invention uses thermoplastic polyurethane (TPU) as the porous matrix of super-hydrophobic foam. TPU is a polymer that is easily obtained, has high hydrophobicity and high chemical stability. The porous matrix is ​​obtained by a thermal shock non-solvent induced phase separation method with the help of additional water, and the contact angle is 134 °. In order to further improve the hydrophobicity of foam, a modified solution containing silicon dioxide nanoparticles and polydimethylsiloxane (PDMS) is used. Silica nanoparticles provide nano-scale roughness for the film, and PDMS acts as an adhesive to fix silicon dioxide nanoparticles on the foam. The modified foam shows super-hydrophobicity, and the water contact angle is 155 °. The TPU foam can be used as a selective filtration membrane to achieve oil-water separation, and the 41.2m 3 m 2 h -1 efficiency.

[0076] In summary, the superhydrophobic TPU foam for oil-water separation and the preparation method thereof provided in the embodiments of the present invention are simple to manufacture, have high oil-water separation efficiency, strong reusability, low cost, high efficiency, and have good long-term application and promotion prospects.

[0077] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing super hydrophobic TPU foam for oil-water separation, characterized in that: The following steps are involved: S1, preparing a porous matrix of superhydrophobic thermoplastic polyurethane, i.e. TPU foam; S2, modifying the porous matrix to obtain super-hydrophobic TPU foam; Wherein, step S1 specifically includes the following steps: S101, mixing TPU particles with dioxane at a ratio of 0.03-0.05 g / mL, stirring to form a uniform solution; S102, cooling the uniform solution obtained in step S101 to room temperature, placing it in a stirring kettle, adding deionized water in a volume ratio of 2:100-4:100, stirring, and obtaining a mixed solution; S103, cooling the mixed solution obtained in step S102 at a temperature of -8 to -4°C until the TPU is completely phase-separated; S104, placing the mixture obtained in step 103 in a freeze-drying container at 80° C. and 8 Pa for 72 hours to obtain a porous matrix of superhydrophobic TPU foam; Step S2 specifically includes the following steps: S201, mixing PDMS and silica nanoparticles in a mass ratio of 1:3-1:5 to obtain a solid mixture of PDMS and silica nanoparticles; S202, mixing the solid mixture of PDMS and silica nanoparticles obtained in step S201 with ethanol at a ratio of 0.2-0.6 g / 100 mL, stirring to obtain a uniform solution; S203, immersing the porous matrix of the super-hydrophobic TPU foam obtained in step S1 into the uniform solution obtained in step S202; S204, placing the porous matrix of the super-hydrophobic TPU foam immersed in step S203 in a 60° C. forced air oven for 1-2 hours to promote ethanol volatilization and PDMS curing, so that the silica nanoparticles adhere to the porous matrix surface of the super-hydrophobic TPU foam to obtain a super-hydrophobic TPU foam.

2. The method for preparing super hydrophobic TPU foam for oil-water separation according to claim 1, characterized in that: In step S101, the stirring temperature is 35-40° C. and the stirring time is 3-4 hours.

3. The method for preparing super hydrophobic TPU foam for oil-water separation according to claim 1, characterized in that: In step S102, the stirring rate is set to 400-600 rpm, and the stirring time is 2-3 hours.

4. The method for preparing super hydrophobic TPU foam for oil-water separation according to claim 1, characterized in that: In step S103, the mixed solution obtained in step S102 is placed in a refrigerator at a temperature of -8 to -4°C and cooled for 12 to 14 hours to achieve complete phase separation of TPU.

5. The method for preparing super hydrophobic TPU foam for oil-water separation according to claim 1, characterized in that: In step S202, the stirring temperature is 60-70°C and the stirring time is 1-2 hours to obtain a uniform solution.

6. The method for preparing super hydrophobic TPU foam for oil-water separation according to claim 1, characterized in that: In step S203, the immersion time is 80-120 seconds.

7. A super-hydrophobic TPU foam prepared by the method for preparing a super-hydrophobic TPU foam for oil-water separation according to any one of claims 1 to 6, characterized in that: Thermoplastic polyurethane, namely TPU, is used as a porous matrix of super-hydrophobic foam, and silicon dioxide nanoparticles are attached to the porous matrix surface of the super-hydrophobic TPU foam to obtain the super-hydrophobic TPU foam.